Analisis Wacana Kritis terhadap Representasi Bansos di Indonesia: Pendekatan Berbasis Korpus - Imamah, Fitria Habibatul; Kharirin, Nur (SULUK : Jurnal Bahasa, Sastra, dan Budaya, 2025)
Social assistance (bansos) constitutes one of the key instruments in Indonesia’s poverty alleviation policies. However, beyond its role as a welfare intervention, bansos has also emerged as a complex social discourse encompassing issues of distribution, justice, political dynamics, and the abuse of power. This study aims to uncover the representation of bansos discourse in Indonesia by employing a corpus-based critical discourse analysis approach. The data utilized in this study is drawn from the LCC Indonesia 2023 corpus, comprising 573 million tokens across 43 texts, analyzed using the CQPweb software. A mixed-methods approach combining both quantitative and qualitative techniques through corpus linguistics and critical discourse analysis was applied. The Qindings indicate that bansos is generally represented in a positive light, as a form of assistance and a solution to welfare-related issues. Nevertheless, the discourse also carries negative connotations, particularly in relation to corruption, political manipulation, and inequities in distribution.